2020
DOI: 10.1002/adfm.202004330
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Phase Engineering of Nickel Boride‐Hydroxide Nanoparticles toward High‐Performance Water Oxidation Electrocatalysts

Abstract: The development of earth‐abundant and efficient oxygen evolution reaction (OER) electrocatalysts is necessary for green hydrogen production. The preparation of efficient OER electrocatalysts requires both the adsorption sites and charge transfer on the catalyst surface to be suitably engineered. Herein, the design of an electrocatalyst is reported with significantly enhanced water oxidation performance via dual‐phase engineering, which displays a high number of adsorption sites and facile charge transfer. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…High‐resolution Ni 2p spectra demonstrate a single valence state of +2; however, Fe and Co exhibit a mixed‐valence state of +2, +3, and 2+ metallic states, respectively (Figure 9E‐G). 37‐40 The mixed‐valence states of Fe and Co may be suitable for efficient electrochemical redox reactions.…”
Section: Resultsmentioning
confidence: 99%
“…High‐resolution Ni 2p spectra demonstrate a single valence state of +2; however, Fe and Co exhibit a mixed‐valence state of +2, +3, and 2+ metallic states, respectively (Figure 9E‐G). 37‐40 The mixed‐valence states of Fe and Co may be suitable for efficient electrochemical redox reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, surface oxidation will additionally affect MBenes' bioactivity. [56] Surface Pourbaix diagrams combined with the selectivity analysis revealed that several MBenes (CrB, MoB, or Mo 2 B) can resist surface oxidation, regardless of pH. [33] Further active tuning of MBenes' properties is crucial for their application in many fields.…”
Section: Applications Envisioned For Mbenesmentioning
confidence: 99%
“…Nickel boride nanostructures have also been shown to be very active in water oxidation by providing a large number of adsorption sites and facile charge transfer. The chemical etching process enables the formation of a metallic nickel boride decorated with hydroxide adsorption sites to stabilize intermediates formed in the OER reaction . Many other interesting catalytic phases and morphologies have been presented in the literature.…”
Section: Applications Of Metal-boride-derived 2d Nanostructuresmentioning
confidence: 99%
“…In this Perspective, we summarize the history, chemical bonding, and crystal structure of both bulk metal borides and the corresponding 2D nanostructures. , We emphasize various strategies proposed to synthesize metal-boride-derived 2D nanostructures and ultrathin films. ,,,, We also present newly developed insights upon revisiting the chemistry of AlB 2 -type metal diborides. ,,,,, Synthetic challenges toward nanostructures of metal diborides, pseudo-metal diborides, MAB phases, and 2D MBenes are summarized and discussed in detail. ,,,,− Later, attention is drawn towards the effect of nanoscaling on catalytic, electrochemical, transport, optical, and mechanical properties. ,,,,,,,,, Our emphasis is not only on the synthesis and properties, but also on diverse potential applications, such as energy storage in batteries, ,, hydrogen storage and production, ,,,, sensors, ,, propellants, combustion and fuels, and biomedicine. , Finally, this Perspective summarizes and presents an outlook on the intriguing aspects, missing links, and some of the remaining challenges and opportunities in the field of metal-boride-derived 2D nanostru...…”
mentioning
confidence: 99%